1980
DOI: 10.1111/j.1365-2605.1980.tb00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Metabolic Effects of the Anti‐Fertility Agent, Gossypol, on Various Reproductive Organs of Male Mice

Abstract: In order to evaluate the short term metabolic effects of gossypol on the testes as well as any possible effects on the secondary sex organs, Balb C mice were injected subcutaneously with various doses of gossypol (0.25-25.0 mg/kg body weight) in corn oil for 10 days. Wet weights of several different secondary sex reproductive organs decreased during gossypol treatment. However, wet weights of the testes during treatment remained equal to or greater than control values. Following 10 days of gossypol treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 21 publications
4
7
1
Order By: Relevance
“…The results of the present study in the Parkes strain mouse indicate that the administration (20 or 40 mg/ kg body weight) of gossypol did not induce alterations in testicular weight, but caused a significant reduction in the weight of the seminal vesicle; this is in agreement with the findings in other strains of mice (COULSON et al, 1980;HUNT and MITTWOCH, 1984). The general appearance of the mice suggests that gossypol had probably no effect on the general condition of the animals during the period of treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the present study in the Parkes strain mouse indicate that the administration (20 or 40 mg/ kg body weight) of gossypol did not induce alterations in testicular weight, but caused a significant reduction in the weight of the seminal vesicle; this is in agreement with the findings in other strains of mice (COULSON et al, 1980;HUNT and MITTWOCH, 1984). The general appearance of the mice suggests that gossypol had probably no effect on the general condition of the animals during the period of treatment.…”
Section: Discussionsupporting
confidence: 91%
“…HAHN et al (1981) reported that gossypol treatment does not induce antifertility effects in mice. According to COULSON et al (1980) and HUNT and MITTWOCH (1984) in mice, the administration of gossypol causes a reduction in both the number of spermatozoa in the epididymis and the weight of the accessory reproductive organs. On the other hand, WANG et al (1979) found no adverse effect of gossypol on accessory glands in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the estimated weights of testes of the gossypol-treated rabbits (Table 2) disagrees with the findings observed in rams (Kramer et al, 1991) and bulls (Velasquez-Pereira et al, 1998) but agrees with those noted in mice (Coulson et al, 1980). A possible increase in water retention in seminal plasma of the gossypol-treated rabbits as indicated by the increase of albumin and unpublished) could have contributed at least in part to this increase in weights of testes.…”
Section: Estimated Testes Weight Reaction Time and Semen Qualitycontrasting
confidence: 58%
“…According to the Chinese [17], gossypol is believed to act at the level of the testis. On the other hand, mice injected with 12.5 or 25 mg/kg of gossypol for 10 days exhibit a statistically significant decrease in the epididymal sperm count [6] and gossypol injected into the epididymal fat pad of the rat causes a decrease in epididymal sperm motility within 24 hr [8]. Furthermore, distal migration of the cytoplasmic droplet from the neck region to the distal end of the midpiece, a phenomenon generally viewed as a function of epididymal sperm maturation [3], is impaired in gossypol-treated rats [4].…”
Section: Discussionmentioning
confidence: 99%